The Formation and Morphology of Nanoparticle Supracrystals. (23rd May 2016) - Haubold, Danny; Reichhelm, Annett; Weiz, Alexander; Borchardt, Lars; Ziegler, Christoph; Bahrig, Lydia; Kaskel, Stefan; Ruck, Michael; Eychmüller, Alexander
Abstract : Supracrystals are highly symmetrical ordered superstructures built up from nanoparticles (NPs) via self‐assembly. While the NP assembly has been intensively investigated, the formation mechanism is still not understood. To shed some light onto the formation mechanism, one of the most common supracrystal morphologies, the trigonal structures, as a model system is being used to investigate the formation process in solution. To explain the formation of the trigonal structures and determining the size of the supracrystal seeds formed in solution, the concept of substrate‐affected growth is introduced. Furthermore, the influence of the NP concentration on the seed size is shown and our investigations from Ag toward Au are extended. Abstract : Trigonal supracrystals are an ideal system to investigate the self‐assembly of nanoparticles in solution into highly symmetrical structures. The proposed substrate‐affected growth mechanism allows determining the size of the crystal seeds built up in solution. The seed size is tuned by the change of the preparation parameters.